Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Asymmetric microbial community reassembly under 7-year experimental precipitation decouples soil carbon storage in a coastal wetland - Run Dang; Leilei Xiao; Lifeng Zhou; Jian Liu; Zhenghao Liang; Yan Wang; Weimin Song; Xiaojie Wang; Xiaojing Chu; Xiaoshuai Zhang; Yang Song; Wanlin Song; et al. (Environmental Research, 2026)

Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Methane production related to microbiota in dairy cattle feces - Jian Liu; Meng Zhou; Lifeng Zhou; Run Dang; Leilei Xiao; Yang Tan; Meng Li; Jiafeng Yu; Peng Zhang; Marcela Hernández; Eric Lichtfouse (Environmental Research, 2025)

Microbiota-induced asymmetry in coastal methane emission potential under experimental precipitation gradients - Lifeng Zhou; Lirong Zhang; Run Dang; Guangxuan Han; Jian Liu; Meng Zhou; Leilei Xiao (Environmental Research, 2025)

Theoretical and Numerical Studies on the Coupling Deformation of Global Lateral Buckling and Walking of Submarine Pipeline - Run Liu; Xintong Hao; Chengfeng Li; Qingxin Li; Zheng Yu; Dang Zhao (Journal of Ocean University of China, 2023)

Biomethane is produced by acetate cleavage, not direct interspecies electron transfer: genome-centric view and carbon isotope - Jian Liu; Jiafeng Yu; Yang Tan; Run Dang; Meng Zhou; Marcela Hernández; Eric Lichtfouse; Leilei Xiao (Bioresource Technology, 2023)